Machine Learning: An artificial intelligence methodology (International Journal of Engineering and Computer Science, 2013)
The problem of learning and decision making is at the core level of argument in biological as well as artificial aspects. So scientist introduced Machine Learning as widely used concept in Artificial Intelligence. It is the concept which teaches machines to detect different patterns and to adapt to new circumstances. Machine Learning can be both experience and explanation based learning. In the field of robotics machine learning plays a vital role, it helps in taking an optimized decision for the machine which eventually increases the efficiency of the machine and more organized way of preforming a particular task. Now-a-days the concept of machine learning is used in many applications and is a core concept for intelligent systems which leads to the introduction innovative technology and more advance concepts of artificial thinking.